Pengaruh Penilaian Kerja Terhadap Kinerja Karyawan Melalui Pengembangan Karir Karyawan - Iftitakhul Baroroh; Ayu Sufi Oktaviya; Fitriya Eka Nur Rahmadani; Ayu Lucy Larassaty (Journal of Student Research, 2023)
Employees are the main factor that is very important in an organization to achieve organizational goals. Satisfactory performance of employees does not appear instantly but requires continuous evaluation. The objectives of this study are as follows: (1) to find out and analyze the effect of performance appraisal on employee performance, (2) To find out and analyze the effect of performance appraisal on employee career development, (3) To find out and analyze the effect of career development on employee performance. The research method used is a quantitative research method using a descriptive approach. Sampling in this study used a purposive sampling technique by distributing questionnaires to collect primary data. The population in this study are employees of PT. Surya Artha Sentosa Mojokerto. The number of employees of PT. Surya Artha Sentosa is 125 people with a research sample of 55 respondents. Based on the research results, the Job Assessment variable has an effect on Career, then Job Appraisal has an effect on Employee Performance, and Career Development has an effect on Employee Performance.